Suffering with dementia: the other side of "living well" - Bartlett, Ruth; Windemuth-Wolfson, Lore; Oliver, Keith; Dening, Tom (Cambridge University Press, 2017)
In this editorial, we challenge the current understanding of “Living Well with Dementia.” Such discourse introduces the possibility of not living well with the condition or even of “living badly with dementia.” Numerous words might be relevant here – grief, pain, anguish, depression – but in this editorial we consciously use the word “suffering.” This term is used for two reasons; one, because it captures the attributes of other more limited words, and, two because the language of “suffering” is contentious, making it suitable for debate. We speak of suffering, not to deny the positive aspects of life with dementia or to concentrate just on the negative, but to redress the balance that is disturbed by a relentlessly positive view of living with the condition. Our aim is to promote a more realistic understanding of the dementia experience, one based on actualities and evidence rather than presumption and sentiment.